The effect of mineral content on the degree of deviation from radioactive equilibrium in the ancient uranium ores of the Ukraine - Valter, A.A.; Dikiy, N.P.; Dovbnya, A.N.; Lyashko, Y.V.; Pisansky, A.I.; Storizhko, V.E. (Вопросы атомной науки и техники, 2007)
The degree of radioactive nonequilibrium of ores was found to increase in the following order in accordance with the varying mineral content: relatively coarse-grained uraninite (UO₂<n<₂.₂₅) - coffinite (USiO₄), brannerite (UTi₂O₆) - secondary finegrained coffinite, brannerite-secondary minerals of thin veins, boltwoodite ((Ca,Na,K)(UO₂)[SiO₃OH]1.5H₂O), and membranous uraninite (UO₂.₂₅). This is ascribed to a different loss of radioactive recoil atoms by crystals because of real crystals dimensions and defects and features of ideal atomic structure of minerals.